2012
DOI: 10.1097/ta.0b013e318241f073
|View full text |Cite
|
Sign up to set email alerts
|

Unique pattern of complications in elderly trauma patients at a Level I trauma center

Abstract: Background Trauma centers are caring for increased proportions of elderly patients. While age and ISS are independently associated with mortality, trauma centers were originally designed to care for seriously injured patients without age-specific guidelines. We hypothesized that elderly patients would have different complication patterns than their younger counterparts. Methods The trauma registry of an ACS-verified level I trauma center was queried for all patients > 14 years of age admitted between 1/2005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 18 publications
5
61
1
3
Order By: Relevance
“…The incidence of lesions to the head segment is significant, as well as fractures of extremities 12 . The mortality rate is higher than in younger individuals, especially in the presence of concomitant diseases and the need for specific treatment [12][13][14] . In a previous study we compared patients aged above and below 60 years and observed a higher incidence of severe intracranial lesions, such as subdural hematomas, cerebral contusions and subarachnoid hemorrhage in the group of patients with more advanced age 14 …”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The incidence of lesions to the head segment is significant, as well as fractures of extremities 12 . The mortality rate is higher than in younger individuals, especially in the presence of concomitant diseases and the need for specific treatment [12][13][14] . In a previous study we compared patients aged above and below 60 years and observed a higher incidence of severe intracranial lesions, such as subdural hematomas, cerebral contusions and subarachnoid hemorrhage in the group of patients with more advanced age 14 …”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…4,5 In fact, a linear relationship between advancing age and increasing mortality after injury has been described, with the oldest patients experiencing the highest mortality rates. 6,7 Significant advancements have been made in the therapy of cancer and heart disease. In particular, emphasis on these 2 leading killers has long resulted in a disproportionate allocation of research funding.…”
mentioning
confidence: 99%
“…2 An increase in middle-aged and geriatric admissions to trauma centers is anticipated, 3,4 and multiple studies have shown that advanced age is associated with poor outcome after injury. 5,6 Specifically, injured patients aged 40 to 45 years reportedly have higher complication and mortality rates than younger patients. 4,5 In fact, a linear relationship between advancing age and increasing mortality after injury has been described, with the oldest patients experiencing the highest mortality rates.…”
mentioning
confidence: 99%
“…Multiple factors, including magnitude of injury [11] and age [12], can affect the outcomes of trauma. In this context, we examined the impact of injury severity and age on the rates of TE.…”
Section: Te Correlate Significantly With Different Parametersmentioning
confidence: 99%